Lifelong learning after school motivation program for SPM Students, Sekolah Menengah Kebangsaan Hulu Kelang Km 7, Jalan Hulu Kelang, 68000 Ampang, Selangor - Abdul Razak, Mohd. Abbas (2016)
This motivation program was conducted for students who will be sitting for their SPM Examinations this year in 2016. The slides were designed to explain the holistic concept of education. Besides that, they are meant to motivate the students to learn from varied sources. The outlets for education and learning were also explained quite extensively.